Stable ankle after modified brostrom technique using one anchor with double suture at Sanglah Hospital: a case report - Subawa, I. Wayan; ., Dwiwahyonokusuma; Mahardika Putra, I. Gede (International Journal of Research in Medical Sciences, 2020)
Ankle sprains are commonly seen injuries among athletic and young population, and it is necessary to stabilize the patient ankle as soon as possible. Authors report the cost-effective option of using a modified Brostrom technique with one suture anchor in a limited resource setting. Case a 24- year-old male came to the orthopaedic clinic with chief complaint of left ankle pain for the past 2 weeks after jumping and landing in a twisted position. Patient also complained of unstable ankle after the fall. On physical examination, the ankle showed tenderness and instability when anterior drawer test was performed. The patient was diagnosed with lateral ankle instability. This case report describes a modification to the original Brostrom procedure using one suture anchor to anatomically reconstruct the lateral ankle ligaments in treating high demand patient who have lateral ankle instability. After six months follow up, the patient has shown significant improvement on his left ankle. Despite of all the modifications of Brostrom procedure, the use of more suture anchors or sophisticated technique such as arthroscopy might result in increasing cost. Reasonably good outcome can still be achieved with modified Brostrom procedure that utilizes minimal incision, simple steps, and single suture anchor. Due to its cost-effectiveness, authors believe that modified Brostrom technique with one suture anchor is an effective and practical treatment option for lateral ankle instability. Brostrom technique using suture anchors as shown here can provide similarly good outcomes compared with other more complex techniques.